Effects of dietary Sel-Plex supplement on growth performance, hematological and immunological parameters in Siberian sturgeon (Acipenser baerii Brandt, 1869) - Gholizadeh Zare Tavana, B.; Banaee, M.; Yousefi Jourdehi, A.; Nematdoost Haghi, B.; Seyed Hassani, M. (2019)
Selenium is one of the most essential trace elements in fishes. Therefore, determining the optimal level of selenium in the fish diet is one of the main concerns of researchers. This study investigated the effects of Sel-Plex (Selenium yeast) supplement on the hematological parameters and immunological parameters, and growth performance in Siberian Sturgeon, Acipenser baerii. The Siberian Sturgeon fed with diets supplemented with 0 (control), 5, 10 and 15 g kg-1 Sel-Plex feed for 8 weeks. Growth performance, hematological parameters, total immunoglobulin, alternative complement activity (ACH50), C3 and C4 levels and lysozyme activity were measured at the end of the experiment. No significant differences have been observed (p>0.05) in weight gain (WG), specific growth rate (SGR), feed conversion ratio (FCR) and condition factors (CF) in the fish fed with different concentrations of Sel-Plex supplement when compared with the control group. The results showed that administration of 10 g Sel-Plex in this ﬁsh signiﬁcantly increased erythrocyte, hemoglobin levels, hematocrit value, leukocytes, and lymphocytes counts. However, neutrophils of fish administrated with 10 and 15 g dietary Sel-Plex significantly decreased. The results revealed that Sel-Plex significantly increased total immunoglobulin, ACH50, C3, and lysozyme activities in the supplemented groups compared with the control. Plasma C4 levels in the fish fed with 5 and 15 g Sel-Plex were significantly higher than the control fish. The results of this study suggest that dietary Sel-Plex supplement at levels ≤15 g kg-1 diet increased some hematological indices and improved the innate immune parameters of the Siberian Sturgeon, without affecting their growth performance. Published